PosterChild: Blend‐Aware Artistic Posterization - Chao, Cheng‐Kang Ted; Singh, Karan; Gingold, Yotam (Computer graphics forum, 2021)
Posterization is an artistic effect which converts continuous images into regions of constant color with smooth boundaries, often with an artistically recolored palette. Artistic posterization is extremely time‐consuming and tedious. We introduce a blend‐aware algorithm for generating posterized images with palette‐based control for artistic recoloring. Our algorithm automatically extracts a palette and then uses multi‐label optimization to find blended‐color regions in terms of that palette. We smooth boundaries away from image details with frequency‐guided median filtering. We evaluate our algorithm with a comparative user study and showcase its ability to produce compelling posterizations of a variety of inputs. Our parameters provide artistic control and enable cohesive, real‐time recoloring after posterization pre‐processing.